DNA Methylation Readers and Cancer: Mechanistic and Therapeutic Applications - Mahmood, Niaz; Rabbani, Shafaat A. (Frontiers in Oncology, 2019)
DNA methylation is a major epigenetic process that regulates chromatin structure which causes transcriptional activation or repression of genes in a context-dependent manner. In general, DNA methylation takes place when methyl groups are added to the appropriate bases on the genome by the action of ‘writer’ molecules known as DNA methyltransferases. How these methylation marks are read and interpreted into different functionalities represents one of the main mechanisms through which the genes are switched ‘ON’ or ‘OFF’ and typically involves different types of ‘reader’ proteins that can recognize and bind to the methylated regions. A tightly balanced regulation exists between the ‘writers’ and ‘readers’ in order to mediate normal cellular functions. However, alterations in normal methylation pattern is a typical hallmark of cancer which alters the way methylation marks are written, read and interpreted in different disease states. This unique characteristic of DNA methylation ‘readers’ has identified them as attractive therapeutic targets. In this review, we describe the current state of knowledge on the different classes of DNA methylation ‘readers’ identified thus far along with their normal biological functions, describe how they are dysregulated in cancer, and discuss the development of various anti-cancer therapies that are currently being developed and evaluated for targeting these proteins.